A Critical Discourse Analysis of Ideological Terror Attacks in Selected Media Reports - Aliwy Mohammed Alhusseini , Hashim (Journal of College of Education, 2020)
This study is sought to investigate the media coverage of the latest wave of attacks that struck New Zealand and Sri Lanka in the early months of 2019. It is believed that certain hidden messages and ideologies, that need to be explored, were embedded behind such attacks. To unmask such ideologies that embedded in the language used in media, the current study employs a critical qualitative data analysis based on Fairclough’s linguistic model (2001) and van Dijk’s model of the ideological square (2006). For more emphasis on data analysis, two articles from two newspapers are selected for this study to shed light on the news of the consequences of these attacks from outside their regional borders. The first one is the "Daily Sabah" from Turkey, and the other is the "New York Times" from America. The findings of the linguistic investigation reveal that these newspapers have many similarities and dissimilarities in the way they publish their news. Both newspapers utilise the concepts of "nominalization" and "negation" for the same function. By contrast, these newspapers differently employ "overwordings" and "pronouns" in publishing the news of the attacks. As for the ideological analysis, the Daily Sabah highlights the negative image of the perpetrators of New Zealand and Sri Lanka attacks, whereas the New York Times sheds light on the positive image of its journalists. Lastly, the study divulges the significant link between the linguistic features and ideological strategies in examining the selected media discourses.
Keywords: Terror Attacks, Fairclough’s linguistic model, Linguistic Features, Ideological Strategies